2017
DOI: 10.1111/sifp.12035
|View full text |Cite
|
Sign up to set email alerts
|

Providers, Unmarried Young Women, and Post‐Abortion Care in Kenya

Abstract: Young women and girls in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Additionally, while community beliefs and attitudes contribute to abortion stigma, available evidence indicates that provider bias can also be a powerful careseeking deterrent; as such, future research should include both community members and health providers to better document and understand the impact of abortion stigma in diverse contexts. 12,15,18,19 Limitations While FGD facilitators were not staff of the three partner organisations, participants may have tried to provide the responses they believed the researchers desired. As induced abortion is a taboo subject in DRC, social desirability bias may also have influenced participants' responses, especially in the early negative reactions to women who induce abortion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while community beliefs and attitudes contribute to abortion stigma, available evidence indicates that provider bias can also be a powerful careseeking deterrent; as such, future research should include both community members and health providers to better document and understand the impact of abortion stigma in diverse contexts. 12,15,18,19 Limitations While FGD facilitators were not staff of the three partner organisations, participants may have tried to provide the responses they believed the researchers desired. As induced abortion is a taboo subject in DRC, social desirability bias may also have influenced participants' responses, especially in the early negative reactions to women who induce abortion.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although there is limited empirical evidence regarding the health impact of abortion stigma, many researchers have hypothesised that the threat of these social costs and desire for confidentiality could influence women to seek clandestine, unsafe abortion services or delay or avoid life-saving post-abortion care (PAC). 9,10,12,[15][16][17][18][19][20][21] For example, despite recent legislation permitting abortion in certain circumstances, a quarter of maternal deaths in Kenya have been attributed to complications from unsafe abortions. 22 Women in Kenya pursued abortions outside of facilities as they believed the social risk associated with being identified as having induced an abortion outweighed the physical risk of pursuing an unsafe, but potentially more discrete, abortion.…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence that women experience poor person-centered abortion care around the globe, a significant limitation in the literature is the lack of a standardized scale to assess person-centered abortion care (PCAC). In Kenya, there are few studies that focus on patient experiences of care, with most studies qualitative in nature [4,[10][11][12]. Standardized measures are important for quality improvement efforts, designing and evaluating health system and policy improvements, identifying the unmet need of the most vulnerable populations, and for advocacy.…”
mentioning
confidence: 99%
“…Religious norms and the view that the early fetus has a moral right to life count against providing abortion; the interests of the pregnant woman count for it. This kind of experienced conflict has been described in other developing countries, such as Kenya [20]. Similarly, a study from South Africa indicated that abortion providers formed their views on abortion in light of personal, moral and religious factors [21].…”
Section: Balancing Allegiances and Concernsmentioning
confidence: 94%